Evaluation of E-Payment Process Embraced By Micro and Small Enterprises of Nagpur City (International Journal of Food and Nutritional Sciences, 2022)
This study presents the findings from interviews with 25 Small and Medium Enterprises (SMEs) in Nagpur's various industry sectors that now use an electronic payment system (EPS). From the viewpoints of owner-managers in various business sizes and industries, this study explores how Nagpur SMEs adopt and develop the EPS process, as well as its prerequisites that would aid them with such adoption. Each participant in this study underwent semi-structured interviews, and the interview transcripts were then thematically analysed. The results of this study show that SMEs were embracing EPS at an early stage, assisted by unofficial decision-making procedures. The results demonstrate that the introduction of the current EPS was mostly ad hoc and unsupported by a formally stated plan. Owner-manager expertise, abilities, and experience with technology are a factor influencing SMEs' adoption of EPS. Observing the EPS operations of other companies in their industry sector and then copying and adapting them for their own use is the approach that SMEs typically utilise to acquire this expertise. The age of owner-managers and a lack of leadership expertise are two issues that come with adopting and implementing EPS.